2013
DOI: 10.4012/dmj.2012-306
|View full text |Cite
|
Sign up to set email alerts
|

Influence of light irradiation on Vickers hardness of dual-cure cement polymerized under restorations

Abstract: This study evaluated, by measuring Vickers hardness (Hv), the effects of these factors on the degree of polymerization of dual-cure cement (Panavia F2.0) placed under a restoration: light transmission property of restoratives materials, distance from the directly irradiated surface, and elapsed time after light irradiation. Two materials were used for the restoration: silver-palladium-copper-gold alloy (Alloy) versus zirconia (ZR). Restorations were cemented on bovine enamel by dual-cure cement. At 30 min, 2 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Hardness is an intrinsic property of materials independent of the hardness test methods employed [36]. e VH test was chosen for the present study which is analogous to the previous studies [37][38][39]. Differences in hardness between the top and bottom surfaces of the specimen were frequently used to detect the polymerization, but the present study employed a different specimen design (much thinner than those in the published studies).…”
Section: Resultsmentioning
confidence: 98%
“…Hardness is an intrinsic property of materials independent of the hardness test methods employed [36]. e VH test was chosen for the present study which is analogous to the previous studies [37][38][39]. Differences in hardness between the top and bottom surfaces of the specimen were frequently used to detect the polymerization, but the present study employed a different specimen design (much thinner than those in the published studies).…”
Section: Resultsmentioning
confidence: 98%
“…These results are consistent with those reported previously. A study by Shiomuki et al [38] on the Vickers microhardness of Panavia F dual-cure resin cement through a zirconia disc showed no significant differences in microhardness between the areas exposed to direct light and those away from light.…”
Section: Discussionmentioning
confidence: 99%
“…Light activation provides a rapid, ondemand boost to the setting reaction, allowing improved double bond conversion and mechanical properties compared with self-polymerization only. Several studies have indicated substantial improvements in the double bond conversion of methacrylate with sufficient light irradiation compared with less light irradiation 31,32) .…”
Section: Discussionmentioning
confidence: 99%